2021
DOI: 10.1186/s12913-021-06927-x
|View full text |Cite
|
Sign up to set email alerts
|

The risks and benefits of using social media to engage consumers in service design and quality improvement in Australian public hospitals: findings from an interview study of key stakeholders

Abstract: Background Engaging consumers - patients, families, carers and community members who are current or potential service users - in the planning, design, delivery, and improvement of health services is a requirement of public hospital accreditation in Australia. There is evidence of social media being used for consumer engagement in hospitals internationally, but in Australia this use is uncommon and stakeholders’ experiences have not been investigated. The aim of the study was to explore the expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…However, the results represent the lived experience of both healthcare staff and consumers who are experienced in QI partnerships and reflect literature that highlights the tokenistic nature of many CCI efforts in QI. 8,41,42 Despite the differences in importance ratings, overall the study indicated that the framework is applicable to both stakeholder groups, as only one capability description (regarding implementation of QI processes and practices), did not meet the threshold for inclusion for consumers. Additionally, statistical analyses indicated that staff and consumer participants rated items in the same way suggesting that both groups recognize that changes are needed to enhance CCI in QI, with staff needing to champion transformation.…”
Section: Perceived Key Responsibility Of Healthcare Staff and Organiz...mentioning
confidence: 87%
“…However, the results represent the lived experience of both healthcare staff and consumers who are experienced in QI partnerships and reflect literature that highlights the tokenistic nature of many CCI efforts in QI. 8,41,42 Despite the differences in importance ratings, overall the study indicated that the framework is applicable to both stakeholder groups, as only one capability description (regarding implementation of QI processes and practices), did not meet the threshold for inclusion for consumers. Additionally, statistical analyses indicated that staff and consumer participants rated items in the same way suggesting that both groups recognize that changes are needed to enhance CCI in QI, with staff needing to champion transformation.…”
Section: Perceived Key Responsibility Of Healthcare Staff and Organiz...mentioning
confidence: 87%
“…10,11,14,15 Because social media can reach audiences different to those reached by typical engagement methods, it may help grow the pool of people engaged in health service design and QI, and expand or re-imagine engagement strategies beyond the overreliance on 'career consumers. ' 16 Social media-based engagement can also allow consumer representatives, patients and families to connect more easily to organise and advocate for change, 15 which could help overcome potential disconnection between patient populations and their representatives. 17,18 The use of social media for consumer engagement is not without risks.…”
Section: Introductionmentioning
confidence: 99%
“…Engagement methods characterised by relationship building between consumers and service providers (such as co-design) might be more difficult via social media, 11,15 and the public nature of interactions on some social media platforms could expose both individuals and organisations to harms such as bullying, harassment and trolling. 11,15 Concerns about these risks, and a lack of understanding about ways to manage or mitigate them, may stymie efforts to further develop social media as a medium for engagement. 15 To better understand and inform the implementation of social media-based consumer engagement in public hospitals, we explored the following research question:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations